THE IMPACT OF LIGHTING CONDITIONS IN MACHINE-BUILDING WORKSHOPS ON THE FUNCTIONAL STATE OF WORKERS (Symposium on Natural and Applied Sciences, 2026)
The machine-building industry is characterized by high precision, continuous attention, and complex technological operations. During turning, milling, pressing, and assembly processes, workers often handle small parts, fast-moving mechanisms, and operations requiring complex visual control. Therefore, lighting conditions are considered one of the leading factors determining not only work comfort but also the functional state of workers.